DESKRIPSI KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU IPA SMP SEDERAJAT DI KECAMATAN KEPENUHAN HULU - Kalsum, Ummi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to determine the extent of the principals leadership to junior high science teacher performance equal subdistrict kepenuhan Hulu. This study used a qualitative approach and descriptive. The method used was a questionnaire. Date analysis is done by means of date presentation and conclusion. Results of the questionnaire data analysis of school leadership and teacher performance science that is, with the average value of principal leadership of 75,08% with a high information and performance science teacher with an average of 76,97% with a high information.Â Keywords: Descriptive, Leadership Principal, Science Teacher Performance.